2022
DOI: 10.1016/j.brs.2022.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Long term study of motivational and cognitive effects of low-intensity focused ultrasound neuromodulation in the dorsal striatum of nonhuman primates

Abstract: Noninvasive brain stimulation using transcranial focused ultrasound (FUS) has many potential applications as a research and clinical tool, including incorporation into neural prosthetics for cognitive rehabilitation. To develop this technology, it is necessary to evaluate the safety and efficacy of FUS neuromodulation for specific brain targets and cognitive functions. It is also important to test whether repeated long-term application of FUS to deep brain targets improves or degrades behavioral and cognitive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 65 publications
5
31
0
Order By: Relevance
“…for 18-31 minutes after a 20 second sonication of the frontal eye field. 26 Other studies have similarly shown changes in NHP behavior 27 , fMRI [21][22][23] or motor evoked potentials (MEP) in humans 28 that persist for minutes to hours following sonications with durations between 40 and 120 seconds. Thus, our measurement of lateralized behavioral changes adds considerable evidence to a growing consensus that ultrasound can induce durable and reversible changes in neuronal activity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…for 18-31 minutes after a 20 second sonication of the frontal eye field. 26 Other studies have similarly shown changes in NHP behavior 27 , fMRI [21][22][23] or motor evoked potentials (MEP) in humans 28 that persist for minutes to hours following sonications with durations between 40 and 120 seconds. Thus, our measurement of lateralized behavioral changes adds considerable evidence to a growing consensus that ultrasound can induce durable and reversible changes in neuronal activity.…”
Section: Discussionmentioning
confidence: 96%
“…19,20 Proofs of concept of durable changes have been published. [21][22][23][24][25][26][27][28] However, the full strength of ultrasound-programmatic targeting of multiple deep brain regions to induce sustained and region-specific neuroplastic effects in awake subjects (Figure 1b)-has not yet been demonstrated. This demonstration is critical for effective and personalized treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the evidence remains inconclusive and warrants further investigation, this conflicting evidence illustrates the importance of methodological choice (as well as proper controls) in experimental designs when investigating thermal and mechanical effects of ultrasound stimulation. One long-term study investigated stimulation effects in 2 macaques over 2 years (129 and 147 stimulation sessions, respectively; 0.5–7.8 W/cm 2 I SPPA in water, 10.1–156.7 mW/cm 2 I SPTA ) and found no signs of trauma on MRI scans or in behavioral analysis [ 52 ].…”
Section: Clinical Safety Datamentioning
confidence: 99%
“…In addition, dexmedetomidine has been used widely as a sedative agent in fMRI and functional connectivity studies of rodents [ 60 , 140 ] by combining it with isoflurane and/or ketamine. These combinations of procedures were explored in a few studies of monkeys for fMRI [ 141 , 142 ] and functional connectivity [ 86 ], suggesting it may improve the detection sensitivity of BOLD signal in the monkey brain at 3T. In addition, ketamine is a racemic mixture of R- and S- ketamine and both showed suppression effects on fMRI signals in the brain.…”
Section: Effects Of Anesthesia On Cbf and Functional Connectivity Of ...mentioning
confidence: 99%